PENGARUH SERTIFIKASI PENDIDIK TERHADAP PENINGKATAN PUBLIKASI ILMIAH DOSEN DI PERGURUAN TINGGI DI INDONESIA - Muchtar Muchtar (AL-ILMU, 2022)
The Indonesian government since 2008 has implemented a certification policy for lecturers. The lecturer certification policy has the aim of improving the performance of lecturers so that the goal of improving the quality of learning in higher education is achieved. This study aims to analyze the impact of the educator certification program on the performance of lecturers by comparing the differences in the performance of lecturers who already have an educator certificate with lecturers who are not certified educators. This study uses a quantitative and qualitative approach. The quantitative approach uses secondary data analysis using the Difference-in-Difference (DiD) model, Regression Discontinuity Design (RDD), and an online survey of lecturers. Meanwhile, the qualitative approach was carried out with data collection techniques in the form of literature studies and focused group discussions which were analyzed using descriptive thematic methods. The results of the analysis show that the provision of lecturer certification and professional allowances is associated with improving the performance of lecturer publications, although it is still not optimal. To increase the impact of lecturer certification, the government can strengthen lecturers who have been certified educators to understand the performance of the specified lecturers. In addition, the performance reporting in the Lecturer Performance Report (LKD) needs to be added to the minimum achievement rate for each lecturer position and includes aspects of the Tri Dharma.Keywords: educator certification, lecturer performance, impact of certification, Tri Dharma